PENGARUH ATRAKSI WISATA DAN FASILITAS WISATA TERHADAP KEPUASAN PENGUNJUNG DI OBJEK WISATA GOA JATIJAJAR KABUPATEN KEBUMEN 2018 - Nurohman, Aji Ima; Lestari, Hesti (Journal of Public Policy and Management Review, 2018)
This research is motivated by the growth rate of tourism in Kebumen regency is high and not balanced with the improvement of the quality of existing attractions, either in the form of tourist attractions or tourism facilities. The problem in this research is "is there any influence on the tourist attraction and tourism facility to visitor satisfaction at Jatijajar Caves. Specifically, this research is focused on two variables, there is he tourist attractions and tourism facilities. The purpose of this study is to be able to study the influence of these two variables in influencing visitor satisfaction in Jatijajar Caves Kebumen. After conducting a literature review and hypothesis preparation, the data collected through questionnaires on 100 visitors Jatijajar Caves Kebumen that obtained by non-probability sampling technique, especially accidental sampling. Then the data analysis obtained by using linear regression analysis and multiple regression. This analysis includes validity and reliability test, Spearman correlation, simple linear regression, multiple linear regression, and hypothesis testing through t test and F test. F test shows that the variables of tourist attraction and tourism facility have a significant effect on visitor satisfaction. Adjusted R square number is 0,594 indicates that 59,4% variable of visitor satisfaction can be explained by both independent variables. While the remaining 40.6% is explained by other variables outside the two variables used in this research.